Cerebral Microbleeds, Hypertension, and Intracerebral Hemorrhage in Cerebral Autosomal-Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy - Lee, Jung Seok; Ko, KeunHyuk; Oh, Jung-Hwan; Park, Joon Hyuk; Lee, Ho Kyu; Floriolli, David; Paganini-Hill, Annlia; Fisher, Mark (Frontiers in Neurology, 2017)
Background: CADASIL (cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is the most common genetic cause of stroke. In addition to ischemic stroke, CADASIL predisposes to development of cerebral microbleeds (CMB). CMB and hypertension are known to be associated with intracerebral hemorrhage (ICH). The purpose of this study was to analyze the relationships among CMB, hypertension, and ICH in CADASIL. Material and methods: We enrolled 94 genetically-confirmed CADASIL patients from 76 unrelated families at Jeju National University Hospital (Korea) between March 2012 and February 2015. We analyzed CMB presence, number, and distribution on susceptibility-weighted imaging MRI using the microbleed anatomical rating scale (MARS). Multiple logistic regression was used to determine factors associated with the presence of CMB and ICH. Results: CMB were observed in 62 patients (66%), median number CMB per patient was 4 (range 0-121). 22 ICH were found in 16 patients (17%). There was incongruence between the most common site of CMB (thalamus) and that of ICH (basal ganglia). Hypertension was independently associated with presence of CMB (multiple regression OR, 2.71; 95% CI 1.02-7.18, p<0.05), and CMB ≥9 (highest third) was significantly associated with presence of ICH (multiple regression OR=9.50, 95% CI 1.08-83.71, p<0.05). Conclusions: In this CADASIL sample, presence of hypertension was independently associated with CMB presence, and CMB burden was independently associated with ICH. Incongruence of sites for CMB and ICH is currently unexplained and requires further study.